Penggunaan Media Power Point Terhadap Motivasi Belajar Siswa Kelas XI Di SMA Negeri 8 Selayar - Ani; Kasman; Akram, (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2023)
The study of the Effect of PowerPoint Media Use on Student Learning Motivation in Natural Science Subjects (IPA) for Grade XI at SMA Negeri 8 Selayar aims to determine the effect of PowerPoint media use on student learning motivation. This study uses a quantitative approach with an ex post facto design. The population in this study were all 36 grade XI students of SMA Negeri 8 Selayar, who were also used as research samples. Data collection techniques were carried out through observation, questionnaires, and documentation. The results of the study indicate that the use of PowerPoint media has a significant influence on student learning motivation in science subjects, as indicated by the results of the Pearson correlation test with a significance value of 0.000 <0.05. Thus, it can be concluded that PowerPoint media plays an important role in increasing student learning motivation, so it is worthy of continued use in the science learning process..